Evaluasi Usability Website Lembaga Tinggi Pesantren Luhur Malang dengan Metode Usability Testing - Kamal Irsyadillah; Tibyani Tibyani; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Website of the Lembaga Tinggi Pesantren Luhur Malang is a website as a means of da'wah, publication of pesantren activities, history, and online registration of new students. The usability components tested in this study are the components of learnability, efficiency, error and satisfaction. This study uses usability testing, interviews and filling out the system usability scale (SUS) and single easy question (SEQ) questionnaires. All participants in this study were users of the website ranging from 15-17 years old, 18-24 years old and 25-64 years old. Usability testing was conducted on nine respondents to determine the components of learnability, efficiency, and error, to explore the problems faced, interviews and SEQ questionnaires were filled out at the end of usability testing. The SUS questionnaire was filled out to 20 respondents to determine the satisfaction component. The evaluation results show the value of the learnability component (77.7%), the efficiency component (0.00039 goals/sec), the errors component (0.09), the satisfaction component on the SUS questionnaire (74) and the SEQ questionnaire with the highest score of 6.6. This indicates a problem that needs to be identified further. The results of participant interviews showed 6 problems, and 6 recommendations for improvement solutions were given regarding changing the interface and adding features based on the appropriate guidelines.